Zmijewski, Taffler, Springate dan Grover Model : Analisis Model Prediksi Kebangkrutan - M Iswahyudi (Ekuitas: Jurnal Pendidikan Ekonomi, 2022)
This study aims to analyze the differences between the Zmijewski model, the Taffler model, the Taffler model and the Grover model in predicting financial distress in SOEs. BUMNs were chosen because BUMNs that were considered not to make a big contribution to the state budget were even reported to have gone bankrupt. The object of research is BUMN that has listed its name on the Indonesia Stock Exchange from 2016 - 2020. With a total of 16 companies, 90 total observations are obtained. The variable size was measured by the cut-off value in the Zmijewski (X-Score), Taffler (T-Score), Springate (S-Score) and Grover (G-Score) models. The results of the analysis show that the x-score, t-score and s-score show the same results regarding the predictions of 2 SOEs experiencing financial difficulties (GIAA and KRAS), these three models emphasize the company's ability to fulfill obligations to third parties. In addition, Zmijewski (X-Score), Taffler (T-Score), Springate (S-Score) also show a mismatch when used as a predictor of financial failure in the banking sector. Meanwhile, the g-score is a less sensitive model in predicting bankruptcy because it emphasizes the comparison of working capital and profit.